2000
DOI: 10.1034/j.1600-0714.2000.290806.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel defects in primary and permanent teeth of children born prematurely

Abstract: Enamel defects were commoner in preterm children, and post-natal dietary intervention had no effect on their frequency. This is the first study in which enamel defects in both primary and permanent teeth have been studied in the same group of preterm children. At age 1 and 2 yrs, 32 preterm children were examined, and the same group was examined again at 9-11 yrs. As controls, 106 healthy children were examined at 1 and 2 yrs, and 64 of them were randomly selected for comparison. When the preterm children were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
10
27

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(177 citation statements)
references
References 7 publications
14
124
10
27
Order By: Relevance
“…These studies showed a prevalence ranging from 26% to 96% DDE. Many of these studies showed the tracheal intubation as an important risk factor in the determination of DDE in deciduous teeth of children born preterm 11,22,[24][25][26] . The birth of a premature child corresponds in odontogenesis to the late bell stage, time in which the deciduous teeth are in the stage of mineralization of the organic matrix of tooth enamel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed a prevalence ranging from 26% to 96% DDE. Many of these studies showed the tracheal intubation as an important risk factor in the determination of DDE in deciduous teeth of children born preterm 11,22,[24][25][26] . The birth of a premature child corresponds in odontogenesis to the late bell stage, time in which the deciduous teeth are in the stage of mineralization of the organic matrix of tooth enamel.…”
Section: Discussionmentioning
confidence: 99%
“…However, tracheal intubation can lead to damage such as glottis stenosis and tracheal stenosis 7,8 . Oral lesions occur mainly in the buccal mucosa, the hypoglossal nerve, lingual nerve, fractured teeth, defective development of enamel (DDE), disruption of the dental crown, and dental malformations [9][10][11][12][13][14] . Some precautions are recommended to minimize the effect of the tracheal tube into the oral cavity, such as: a) to define a switch back and forth during intubation, and b) to evaluate continuously the quality of the fixing and stabilization the head of the child in order to decrease the tube displacement preventing accidental extubation 15 .…”
Section: Introductionmentioning
confidence: 99%
“…9-11 yaş arası 32 Finlandiyalı ço-cukla yapılan bir çalışmada, zamanında doğan çocuk-ların %36'sında, erken doğan çocukların ise %84'ünde mine defektleri gözlenmiştir. 37 Mine defektlerinin ciddiyeti, gebelik süresinin ve doğum ağırlığının azalması ile artmaktadır. 38 …”
Section: Erken Doğumunclassified
“…Em contrapartida, a opacidade (ou hipocalcificação) é definida como um defeito qualitativo, identificado visualmente como uma anormalidade na translucidez do esmalte, com áreas branco-opacas, amareladas ou acastanhadas, sem perda de continuidade da superfície afetada 24,25 .…”
Section: H I P O P L a S I A D O E S M A L T Eunclassified